2021
DOI: 10.21203/rs.3.rs-51654/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survey of Perceptions and Educational Needs of Primary Care Providers Regarding Management of Patients with Class II and III Obesity in Ontario, Canada

Abstract: Background: Primary care providers (PCPs) are typically the primary contact for patients with obesity seeking medical and surgical weight loss interventions; however, previous studies suggest that fewer than 7% of eligible adult patients are referred to publically funded medical and surgical weight loss interventions (MSWLI)Methods: We performed an anonymous survey study between October 2017 and June 2018 to explore the knowledge, experiences, perceptions, and educational needs of PCPs in Southeastern Ontario … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Despite an increasing number of studies in the last decade describing educational interventions aimed at management of patients with obesity at the UGME level, the ongoing lack of preparedness of graduating medical students and primary care providers to manage patients with obesity suggests that the interventions discussed herein have either had insufficient time to take effect, or have been too sparsely implemented, or both. 8,9 Although we find increasing awareness of this issue encouraging, we note that addressing the obesity epidemic by prioritizing the teaching of primary prevention and management of patients with obesity has been a matter of concern in medical schools in the United States for over 30 years. 59 As such, our finding of only 17 relevant studies in this review likely reflects an ongoing lack of engagement with these concerns and suggests that the necessary changes to medical school curric-…”
Section: Comparison Of Results To Published Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…Despite an increasing number of studies in the last decade describing educational interventions aimed at management of patients with obesity at the UGME level, the ongoing lack of preparedness of graduating medical students and primary care providers to manage patients with obesity suggests that the interventions discussed herein have either had insufficient time to take effect, or have been too sparsely implemented, or both. 8,9 Although we find increasing awareness of this issue encouraging, we note that addressing the obesity epidemic by prioritizing the teaching of primary prevention and management of patients with obesity has been a matter of concern in medical schools in the United States for over 30 years. 59 As such, our finding of only 17 relevant studies in this review likely reflects an ongoing lack of engagement with these concerns and suggests that the necessary changes to medical school curric-…”
Section: Comparison Of Results To Published Literaturementioning
confidence: 95%
“…With obesity being a worldwide epidemic with profound implications on our society's health and wellness, physicians have a professional and social responsibility to assess, manage, and counsel patients with obesity. Despite the requirement to manage patients with obesity in their clinical practice, primary care providers report feeling poorly prepared for this management 8 . Moreover, this lack of preparedness appears to span the entire continuum of medical education with a survey of 40 medical schools in the United States in 2018 demonstrating that U.S. medical schools are not adequately preparing their students to manage patients with obesity 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent studies have shown improvements in BS safety, largely due to the advancements in laparoscopic surgical techniques [37], which also makes this kind of obesity therapy more popular. In contrast as mentioned above, GPs are concerned over providing long-term care [36] due to a lack of knowledge [38, 39] and missing education programs [31, 40]. Educational strategies to address these barriers should target continuous knowledge transfer regarding topics in the long-term treatment after BS.…”
Section: Discussionmentioning
confidence: 99%
“…47 Importantly for this population, shifting away from a weight-centric approach to one focused on wider person-centred outcomes, 48 including maintaining or achieving functional independence, potentially holds benefit for both individuals and service providers. Training for community staff, who often have sustained input with individuals, but feel ill-equipped to discuss weight, 49 could lead to health gains.…”
Section: Role Of Weight Managementmentioning
confidence: 99%